Developmental vulnerability of synapses and circuits associated with neuropsychiatric disorders. (22nd May 2013) - Penzes, Peter; Buonanno, Andres; Passafaro, Maria; Sala, Carlo; Sweet, Robert A.
Abstract Psychiatric and neurodegenerative disorders, including intellectual disability, autism spectrum disorders (ASD), schizophrenia (SZ), and Alzheimer's disease, pose an immense burden to society. Symptoms of these disorders become manifest at different stages of life: early childhood, adolescence, and late adulthood, respectively. Progress has been made in recent years toward understanding the genetic substrates, cellular mechanisms, brain circuits, and endophenotypes of these disorders. Multiple lines of evidence implicate excitatory and inhibitory synaptic circuits in the cortex and hippocampus as key cellular substrates of pathogenesis in these disorders. Excitatory/inhibitory balance – modulated largely by dopamine – critically regulates cortical network function, neural network activity (i.e. gamma oscillations) and behaviors associated with psychiatric disorders. Understanding the molecular underpinnings of synaptic pathology and neuronal network activity may thus provide essential insight into the pathogenesis of these disorders and can reveal novel drug targets to treat them. Here, we discuss recent genetic, neuropathological, and molecular studies that implicate alterations in excitatory and inhibitory synaptic circuits in the pathogenesis of psychiatric disorders across the lifespan.